Comparative selective pressure analysis on mitochondrial protein-coding genes in flying squirrels (Pteromyini) and tree squirrels (Sciurini) - Tu, Feiyun; Qiao, Yaqin; Zhao, Wenjing; Wu, Tong (Mitochondrial DNA. Part A. DNA mapping, sequencing, and analysis, 2025)
Different animal groups with varying locomotion modes may have unique energy requirements. Mitochondria produce adenosine triphosphate (ATP) and reactive oxygen species via oxidative phosphorylation to support organisms energy requirements. The tribes Pteromyini (flying squirrels) and Sciurini (tree squirrels), two closely related taxa within the family Sciuridae, exhibit distinct locomotion modes, energy requirements, and likely face different selective pressures on mitochondrial protein-coding genes (PCGs). We analysed 13 mitochondrial genome sequences from species belonging to the tribe Pteromyini and 117 from species belonging to the tribe Sciurini. Phylogenetic analysis revealed Pteromyini and Sciurini formed a sister relationship within the family Sciuridae. Among the 13 PCGs, exhibited the highest dN/dS values, while showed the lowest. The background selection ratio (ω ) values for six genes ( , , , , , and ) in Pteromyini were lower than the foreground selection ratio (ω ) values observed in Sciurini. A RELAX analysis revealed that , , , and genes experienced intensified in selection strength. BUSTED analysis identified stronger signatures of diversifying selection in and , highlighting amino acid changes. MEME identified episodic diversifying selection at specific sites among eight PCGs. These findings revealed distinct selective pressures on PCGs in flying and tree squirrels.